Decreases in procalcitonin and C-reactive protein are strong predictors of survival in ventilator-associated pneumonia - Seligman, Renato (2006)
Introduction This study sought to assess the prognostic value of the kinetics of procalcitonin (PCT), C-reactive protein (CRP) and clinical scores (clinical pulmonary infection score (CPIS), Sequential Organ Failure Assessment (SOFA)) in the outcome of ventilator-associated pneumonia (VAP) at an early time point, when adequacy of antimicrobial treatment is evaluated. Methods This prospective observational cohort study was conducted in a teaching hospital. The subjects were 75 patients consecutively admitted to the intensive care unit from October 2003 to August 2005 who developed VAP. Patients were followed for 28 days after the diagnosis, when they were considered survivors. Patients who died before the 28th day were non-survivors. There were no interventions. Results PCT, CRP and SOFA score were determined on day 0 and day 4. Variables included in the univariable logistic regression model for survival were age, Acute Physiology and Chronic Health Evaluation (APACHE) II score, decreasing ΔSOFA, decreasing ΔPCT and decreasing ΔCRP. Survival was directly related to decreasing ΔPCT with odds ratio (OR) = 5.67 (95% confidence interval 1.78 to 18.03), decreasing ΔCRP with OR = 3.78 (1.24 to 11.50), decreasing ΔSOFA with OR = 3.08 (1.02 to 9.26) and APACHE II score with OR = 0.92 (0.86 to 0.99). In a multivariable logistic regression model for survival, only decreasing ΔPCT with OR = 4.43 (1.08 to 18.18) and decreasing ΔCRP with OR = 7.40 (1.58 to 34.73) remained significant. Decreasing ΔCPIS was not related to survival (p = 0.59). There was a trend to correlate adequacy to survival. Fifty percent of the 20 patients treated with inadequate antibiotics and 65.5% of the 55 patients on adequate antibiotics survived (p = 0.29). Conclusion Measurement of PCT and CRP at onset and on the fourth day of treatment can predict survival of VAP patients. A decrease in either one of these marker values predicts survival.